Praxiology-Based Entrepreneurship Learning Media: A Framework for Entrepreneurial Value Internalization Among Students - Agung Winarno; Sopingi; Desti Nur Aini; Abdillah Agustya Siwi Nashiro; Nurul Hildha Afifa (Indonesian Journal of Business and Entrepreneurship Research, 2026)
Entrepreneurship education in higher education continues to emphasize knowledge acquisition, while the internalization of entrepreneurial values through goal-directed action and self-reflection has yet to be systematically integrated into the learning process. This study aimed to develop and evaluate a praxiology-based entrepreneurship learning medium designed to support the internalization of entrepreneurial values among university students. The study employed an educational action research design conducted over three cycles: initial inquiry and planning, intervention implementation and monitoring, and intervention refinement based on reflection on the findings from each cycle. Participants were 50 undergraduate students enrolled in an Entrepreneurship course at the Faculty of Economics and Business, Universitas Negeri Malang. The intervention was delivered through Praxiedu, a Learning Management System (LMS) that integrates learning materials, idea–action–consequence mapping, self-assessment, reflective activities, and video podcasts featuring authentic entrepreneurial experiences. Changes in entrepreneurial values were assessed using pre- and post-intervention measures covering five dimensions and were analyzed descriptively and using a paired-samples t test. The findings showed increases across all measured dimensions, with the most pronounced changes observed in self-confidence, which increased from 65% to 87%, and self-motivation, from 62% to 81%. Creativity increased from 58% to 70%, whereas risk-taking and leadership showed more modest changes, rising from 55% to 63% and from 54% to 61%, respectively. During the intervention-refinement stage, the addition of video podcasts featuring authentic entrepreneurial experiences was followed by reports of more realistic and contextually grounded new business ideas among 60% of the students, along with a 12-percentage-point increase in creativity scores compared with the preceding cycle. These findings suggest that the internalization of entrepreneurial values does not develop uniformly and appears to be stronger in dimensions directly supported by self-evaluation, reflection on action, and exposure to authentic experience. The study’s novelty lies in integrating praxiology into LMS-based entrepreneurship education by linking goals, actions, consequences, and reflection as interconnected components of action-oriented entrepreneurial value formation.